Ceramic crowns and sleep bruxism: first results from a randomized trial - Schmitter, Marc; Bömicke, Wolfgang; Behnisch, Rouven; Lorenzo Bermejo, Justo; Waldecker, Moritz; Rammelsberg, Peter; Ohlmann, Brigitte (Journal of Clinical Medicine, 2023)
Background: This randomized clinical trial was conducted to assess whether sleep bruxism (SB) is associated with an increased rate of technical complications (ceramic defects) in lithium disilicate (LiDi) or zirconia (Z) molar single crowns (SCs). Methods: Adult patients were classified as affected or unaffected by SB based on structured questionnaires, clinical signs, and overnight portable electromyography (BruxOff) and block randomized into four groups according to SB status and crown material (LiDi or Z): LiDi-SB (n = 29), LiDi-no SB (n = 24), Z-SB (n = 23), and Z-no SB (n = 27). Differences in technical complications (main outcome) and survival and success rates (secondary outcomes) one year after crown cementation were assessed using Fisher’s exact test with significance level α = 0.05. Results: No technical complications occurred. Restoration survival rates were 100% in the LiDi-SB and LiDi-no SB groups, 95.7% in the Z-SB group, and 96.3% in the Z-no SB group (p > 0.999). Success rates were 96.6% in the LiDi-SB group, 95.8% in the LiDi-no SB group (p > 0.999), 91.3% in the Z-SB group, and 96.3% in the Z-no SB group (p ≥ 0.588). Conclusions: With a limited observation time and sample size, no effect of SB on technical complication, survival, and success rates of molar LiDi and Z SCs was detected.
Gesehen am 20.06.2023
Published: 29 December 2022